Efficiency of mushrooms for food production - fundamental strategic decision-making - Zied, Diego Cunha [UNESP]; Pardo, Jose Emilio; Noble, Ralph; Pardo-Giménez, Arturo (Elsevier, 2024)
This work seeks to understand the relationships between the proximate composition of the substrates and the fruiting bodies, and the yield and cultivation time of the main cultivated mushrooms. To this end, the protein, ash, fiber, fat, and carbohydrate content of the substrate and 10 species of mushroom were evaluated. The bioconversion efficiency was calculated by dividing the dry weight of the substrate by the dry weight of the mushroom, resulting in the ratio of proximate composition. Oyster mushroom (Pleurotus ostreatus) showed the highest efficiency of protein bioconversion ratio (1.86) from substrate to mushroom, while enokitake (Flammulina velutipes) stood out in terms of fiber ratio (15.19), king oyster mushroom (Pleurotus eryngii) in terms of fat ratio (0.15), and button mushroom (Agaricus bisporus) in terms of carbohydrate ratio (59.24). Substrates with higher protein and ash content produce mushrooms with higher protein and fiber content, as verified for the genus Agaricus. The relationship between the proximate composition of substrates and mushrooms may be an important tool to assist in mushroom production costs and strategic decision-making.
Keywords: Agaricus bisporus; Lentinula edodes; Pleurotus ostreatus; Protein; Substrate/mushroom ratio; Yield